Malt volatile compounds (Part I) - Herrmann, Markus; Gastl, Martina; Thiele, Frithjof; Back, Werner (BrewingScience, 2007)
The measurement of the malt volatiles targets Maillard-products, Strecker-aldehydes, higher alcohols and compounds of the lipid metabolism of barley. These substances act as indicators for a multiplicity of technological factors, like proteolysis or thermal load during kilning. The effects of using malts with different loads of volatile compounds for beer production will be discussed in Part II of this publication series. This paper shows the improved method of analysis for these substances and the influence of various malting parameters on the formation of the volatile compounds using a statistically planed experimental design termed Response Surface Methodology. The differences between the formation of the volatiles within typical maltings parameters is very large and concentrations thus differ up to a factor 26. If one considers only malts within brewing specifications a factor of up to 7 still remains. Green malt moisture and germination temperature are the main influencing factors; high germination temperatures are suited to produce malt with low volatile concentrations if higher malting losses are acquiesced.